Dampak pandemi covid-19 terhadap perekonomian usaha Mikro Kecil dan Menengah (UMKM) Kripik Singkong Kelurahan Pandanwangi Kecamatan Blimbing Kota Malang - Mahsuni, Abdul Wahid; Wahono, Budi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The cassava industry center, Pandanwangi Village, Kec. Blimbing, is a fairly developed UMKM and has become the hallmark of the city of Malang. MSMEs are among the fields that feel the effects of the Covid-19 pandemic. The purpose of this study was to determine the economic impact of the COVID-19 pandemic on cassava chip micro, small, and medium enterprises (MSMEs) in Pandanwangi Village. Based on the analysis of the data used descriptively, this research method uses qualitative methods. Data collection was carried out through observation, interviews, and the examination of documents and archives with qualitative descriptive analysis. The results of this study reveal that the impact of the COVID-19 pandemic on the economy of MSME cassava chips in the city of Pandalangi, Malang City, is divided into four aspects, namely, sales, marketing, funding or capital, production, and distribution. However, the government has also made various policies to encourage MSMEs to survive in the face of the CO-19 pandemic. The strategy used by MSME cassava chip business actors in Malang is based on social media and e-commerce. This strategy is considered capable of helping MSMEs in marketing activities and expanding their market in dealing with the CO-19 pandemic.